Essays on the role of experience and learning in post-aquisition performance of emerging market multinational enterprises - Wang, Guanqun (2023)
Emerging market multinationals enterprise (EMNEs) use crossborder merges and acquisitions (CBMAs) to catch up with global market leaders and sustain competitive advantages through exploring the strategic assets of developed markets. Due to being later arrivals to the internationalization stage, EMNEs engaging in CBMAs often face challenges related to the liability of foreignness. Firms learn through the accumulation of international experience and try to overcome challenges by converting international experience to experiential knowledge of foreign markets. However, researchers have not yet thoroughly investigated the effects of learning from experience by the EMNEs when undertaking CBMAs. This thesis explores whether experience matters in the postacquisition performance of EMNEs. It expands the understanding of this ambiguous causal relationship by discussing and empirically testing how and when, and what kind of experience can influence EMNEs’ post-acquisition performance. The framework of this thesis was empirically tested using data mainly from the manufacturing industry of 434 cross-border mergers and acquisitions (CBMAs) conducted by Chinese multinational enterprises (CMNEs) between 2006 and 2017.